Caracterização estrutural e ambiental de bosques de mangue da costa paraense, como subsídios à conservação e qualidade de vida - CARVALHO, Elena Almeida de (Universidade Federal do Pará, 2018)
The mangrove ecosystem is among the most productive in the world and in Brazil, occurs along almost the entire coast, from Amapá to Santa Catarina. In this research, the overall objective was to assess the environmental conditions in three mangrove forests of Pará coast, to identify environmental standards to demonstrate their conservation status and relationship with the quality of life of communities. The specific objectives were: to characterize the floristic composition and structure of mangroves; investigate soil-vegetation interrelations; investigate ways to use and environmental perceptions of human populations with mangroves; and conduct an interdisciplinary and systemic analysis of the floristic characteristics, soil and social in mangroves. The areas chosen were the municipalities of Soure (Marajo Island), Salinópolis and Maracanã (Algodoal Island). We used standardized methods to each topic discussed. As for the floristic composition, species were compatible to what the literature for this region and the prevailing environmental conditions. The woods had a high degree of structural development, and in Soure the highest values were recorded. Soil parameters translated a portion of the local and regional environmental scenario that these mangroves are submitted, and showed great influence on the composition, distribution and abundance of plant species present. Human communities showed diversity of uses of mangroves, having been in Salinópolis the largest variety of records. Environmental awareness about the conservation of this ecosystem, proved to be different between communities, and in Algodoal Island, there were records that showed lesser degree of traditional relationship with it. The interdisciplinary analysis involving physical, biological and anthropogenic components, indicated well preserved mangroves in their natural attributes, however, revealed a degree of threat that comes from only economistic visions for regional development. Warns to the need for actions linked to specific scientific research to detect the degree of threat to this ecosystem, and other coastal zone are subject, as well as public policy, environmental education, organization, supervision and practice of establishing legislation for protected areas and mangroves, for the maintenance of these ecosystems, and improving local communities quality of life.